2018 AIAA Aerospace Sciences Meeting 2018
DOI: 10.2514/6.2018-0932
|View full text |Cite
|
Sign up to set email alerts
|

Modal Analysis of the Surface Pressure Field Around a Hemispherical Turret using Pressure Sensitive Paint

Abstract: Fast-response Pressure Sensitive Paint (PSP) measurements were performed on hemispherical models at transonic flow speeds. Both Proper Orthogonal Decomposition (POD) and Dynamic Mode Decomposition (DMD) were used to analyze the spatially and temporally resolved data. POD was used to isolate the dominant behavior in the data and isolate the dominant frequencies by looking at the temporal coefficient spectra. DMD was then used to further investigate specific frequencies. At St = 0.15-0.2, previously investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The anti-symmetric Modes 1 and 4 have noticeable peaks at St D ≈ 0.18. This is consistent with results obtained in [8,26] and is associated with anti-symmetric vortex shedding. The spectra of modes 2 and 3 for the hemisphere do not have any noticeable peaks.…”
Section: Pod Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…The anti-symmetric Modes 1 and 4 have noticeable peaks at St D ≈ 0.18. This is consistent with results obtained in [8,26] and is associated with anti-symmetric vortex shedding. The spectra of modes 2 and 3 for the hemisphere do not have any noticeable peaks.…”
Section: Pod Analysissupporting
confidence: 93%
“…Mode 4 shows a strong anti-correlation in the wake similar to mode 1, which is again related to the alternating vortex shedding off of the turret. This mode was also seen in [26] where the alternating pockets continued downstream, which in this case, if the wake region was extended downstream, we would expect to see another set of correlated regions, but with a blue region on the positive Z side and a yellow region on the negative Z side. This mode also has anti-correlation between the dome and the wake as was seen in mode 2.…”
Section: Pod Analysismentioning
confidence: 57%
“…Due to the presence of shock and shock-related separation at the surface of a turret, the flow over it under transonic free stream conditions is quite complex. To study the detailed regime of the transonic flow field over a turret, much experimental and numerical work has been performed (Coirier et al 2014;Vorobiev et al 2014;Beresh et al 2016;De Lucca et al 2018;Kamel et al 2019;Weston and Sherer 2019). Vorobiev et al (2014) studied the relationship between shock and relevant separation in a two-dimensional cylindrical turret in wind tunnel experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed a large distortion of the wavefront as the beam transited through the shock region, and the shock located in front of the top of the turret was different from that observed in the 2D cylindrical turret. De Lucca et al (2018) studied the pressure field of transonic flow over a hemisphere tested with pressure-sensitive paint, and the decomposition methods of proper orthogonal decomposition (POD) and dynamic mode decomposition (DMD) were implemented to identify the temporal and spatial characteristics of the flow field. They found that the fluctuation of the wake along the wall-normal direction, which contributed less than the lateral shift of the wake to the flow field, was the second mode feature.…”
Section: Introductionmentioning
confidence: 99%
“…A companion paper [30] uses the same experimental data to alternatively study the dominant flow features using POD and Dynamic Mode Decomposition (DMD) techniques.…”
Section: Introductionmentioning
confidence: 99%